PENERAPAN ALAT PERMAINAN EDUKATIF ULAR TANGGA DALAM MENINGKATKAN KEMAMPUAN BERHITUNG PADA MATERI PERKALIAN BILANGAN MATA PELAJARAN MATEMATIKA - Cahyani, Sindi; Nurwati, Andi; Nadjamuddin, Asriyati (MIDA : Jurnal Pendidikan Dasar Islam, 2025)
This study aims to determine whether the application of educational snakes and ladders game tools can improve the ability to count on the material of multiplication of numbers in Mathematics subjects in class II SDN 4 Limboto, Gorontalo Regency. This type of research is classroom action research. The subjects of this study were class II at SDN 4 Limboto totaling 15 people. The data analysis technique used in this study was analysis of test results and analysis of observation results. Based on the results of the study, it can be concluded that learning Mathematics using educational snakes and ladders game media can improve the ability to count on the material of multiplication of numbers of class II students at SDN 4 Limboto. This is indicated by the learning outcomes of students in cycles I and II which have increased. In cycle I, there were 10 students who were categorized as achieving KKM with a percentage of 66% and in cycle II, 14 students were categorized as achieving KKM with a percentage of 93%. So KKM increased by 27%. This is because in cycle II students have started to improve in the learning process, most students are already at their maximum in their ability to count on the material of multiplication of numbers. So student learning in cycle II has reached the KKM value or the performance indicator that has been set.